2019
DOI: 10.7717/peerj.6225
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and potential of phage therapy against multidrug resistantShigellaspp.

Abstract: Shigella-infected bacillary dysentery or commonly known as Shigellosis is a leading cause of morbidity and mortality worldwide. The gradual emergence of multidrug resistantShigellaspp. has triggered the search for alternatives to conventional antibiotics. Phage therapy could be one such suitable alternative, given its proven long term safety profile as well as the rapid expansion of phage therapy research. To be successful, phage therapy will need an adequate regulatory framework, effective strategies, the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 153 publications
1
26
0
Order By: Relevance
“…Numerous animal have studies demonstrated that phages are able to survive in experimental animals with dysentery. Despite no reports on significant undesirable reactions during the long history of phage therapy in humans,176 phage treatments still need to overcome admission constraints in the main medical repertoire.…”
Section: Novel Therapeutic Strategies For Shigella Treatmentmentioning
confidence: 99%
“…Numerous animal have studies demonstrated that phages are able to survive in experimental animals with dysentery. Despite no reports on significant undesirable reactions during the long history of phage therapy in humans,176 phage treatments still need to overcome admission constraints in the main medical repertoire.…”
Section: Novel Therapeutic Strategies For Shigella Treatmentmentioning
confidence: 99%
“…In terms of controlling bacterial food source pollution, some bacteriophage products have been certified by FDA, such as ListShield TM , EcoShield TM , and SalmoFresh TM (Tang et al, 2019). Currently, ShigaShield TM against Shigella is undergoing FDA and USDA reviews for their safety (Soffer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, after antibiotics were discovered and widely used, only Eastern European countries insisted on phage treatment for infections (Nikolich and Filippov, 2020). In the 21st century, phages against MDR Shigella have been widely investigated (Tang et al, 2019;Kortright et al, 2019). Bernasconi et al proved that three commercially available bacteriophage cocktails could suppress Shigella infections in the human intestine (Bernasconi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to developing new antibiotics, a more desirable strategy is exploring alternative antibacterial agents that are hard to develop resistance. To meet this requirement, scientists have developed bacteriophages, [40][41] quaternary ammonium compounds, [42] and antimicrobial peptides, [43] etc. In recent years, photodynamic therapy (PDT) reagents including both AIEgens and water-soluble CPs have been applied in drug-resistant bacteria killing with the features of minimal invasiveness and side effects, low cytotoxicity and free of drug resistance.…”
Section: Introductionmentioning
confidence: 99%